Upaya Meningkatkan Perilaku Disiplin Siswa melalui Layanan Bimbingan Kelompok - Salmi (Jurnal LENTERA: Jurnal Studi Pendidikan, 2021)
The purpose of this study is to find out how group guidance services can improve student discipline behavior. The approach used in this research is action research with the research subjects of class VIII students who have a low tendency of disciplinary behavior. This research was conducted in three cycles, each cycle consisting of: (1) Preparation of an action plan, (2) Action, (3) Observation, (4) Reflection, Implementation of actions taken by researchers through group guidance using discussions and lectures, film screenings, audio CD and combined with outbound management training showed a significant increase. After the implementation of cycle 1, there was an increase of 8.04% from the initial condition, after cycle 2 there was an increase of 5.40% from the condition after cycle 1 (13.44% from the initial condition), and an increase of 1.08% after cycle 3 (14,52% from the initial condition), so that in all of the 3 cycles there was an increase of 14.52% and all students were in the high criteria of disciplinary behavior. Changes in student behavior include having an understanding of school rules (rules), mental attitude in implementing school rules, and seriousness in obeying school rules